Parental cohesion and hierarchy perceived by riverside people who participate in Bolsa Família Program - Freire, Viviam Rafaela Barbosa Pinheiro; Silva, Simone Sousa da Costa; Pontes, Fernando Augusto Ramos (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This article investigated how people who participate in Bolsa Família Program perceive parental cohesion and hierarchy in a riverside Amazonian context. This is a case study, which was attended by three members of a family group. Sociodemographic Inventory and Family System Test (FAST) were used. The results showed that: mother has a key role in the family, since she is directly involved in the adjustment of cohesion and hierarchy with her children; father represented himself distant from children; and daughter represented herself intimately linked to the mother figure, who had similar perceptions of parental cohesion and hierarchy. It can be concluded that, in this group, the maternal cohesion seems to be favorable to the fulfillment of conditionalities and to the development of the beneficiary child.